The mixture material of dried straw and kapok for acoustic treatment for UTeM mosque - Mohd Muzafar, Ismail; Jeefferie, Abd Razak; Ramli, Junid; Nor Aisah, Khalid; Faiz, Arith; Maizatul Alice, Meor Said (IOP Publishing, 2020)
The acoustical requirements in terms of intelligibility and liveliness are dissimilar for both of sounds-recitation and speech on religious subjects at UTeM mosque. To attain an overall satisfactory acoustical performance, it is significant to find an optimum Reverberation Time (RT) and the best directivity, which is the major factors affecting intelligibility and liveliness. This experiment is conduct to gauge the effect of RT by making it a variable, while keeping other factors as non-variable and fulfilling ideal conditions for maximum intelligibility. Bearing in mind, the acoustical problems always occurred in any communication building. To improve the problem, this paper presents the new idea of improvement by using biodegradable sound absorber materials which is the mixture of dried rice straw and kapok.